VALIDASI METODE PENGUJIAN KADAR UREA DALAM AIR BUANGAN DENGAN PEREAKSI PDAB MENGGUNAKAN SPEKTROFOTOMETER UV-VIS - Risma Sari; Ririn Trisna Yusuf (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
Urea in water is not very good for the environment and also living things because it can cause odor and can damage body tissues. This study aims to verify the test method of determining urea levels in wastewater with p-Dimethylamino benzaldehyde reagent using UV-Vis Spectrophotometer. The method used in this study is Spectrophotometry. In this research, several verification parameters will be carried out, namely precision, accuracy, linearity and working range, and detection limits and quantization limits. Based on testing these parameters, the CV (Coefficient Variation) value meets the requirements for precision acceptance, namely CV ≤ CV Horwitz. Accuracy results at spike concentrations were 10%, 20%, 30%, 40% and 50%, respectively 102,608%, 106,540%, 101,713%, 106,409%  and 101,171%. The results of the working range and linearity, R2 = 0.9994. Detection limit 0.0089 and quantization limit 0.0297. Based on the results obtained from the verification, the test method of urea content in water meets the requirements and can be used to determine the level of urea in effluent.